ISenseVR: bringing VR exposure therapy outside the laboratory. Issue 2 (18th June 2019) - Poyade, Matthieu; Morris, Glyn; Taylor, Ian C.; Portela, Victor
Abstract : Purpose: The purpose of this paper is to present the preliminary outcomes of a research which takes gradual exposure in virtual reality (VR) outside the laboratory to empower people with "hidden disabilities" breaking down their barriers towards independent living. It explores the use of VR through smartphones to practically apply gradual exposure to environment stressors that are typically found in busy spaces from one's own safe environment. Design/methodology/approach: Aberdeen International Airport has kindly accepted to take part to this research as a case study. Following a participatory design and usability testing, a semi-controlled seven-day study was conducted among seven individuals with hidden disabilities to assess user acceptance. Findings: Results showed undeniable participants' engagement and enthusiasm for the proposed approach, although further research is needed to increase the presence and improve the overall user experience. Research limitations/implications: The proposed research has been conducted on small cohort of participants outside of a clinical setting. Further engagement with individuals with hidden disabilities is required in order to determine the effectiveness of the proposed approach. Originality/value: This research presents a methodological and technological framework which contributes effectively to the practicality of VR exposure therapy outside of the laboratory setting, from one's own safe place.